Listy Ojców Kapadockich do kobiet - Dybała, Jolanta (Vox Patrum, 2013)
The letters of the Cappadocian Fathers serve as part of the evidence that in the early Church correspondence of its leaders played an essential role in ensuring its proper functioning. Among the addresses of the epistles of Basil the Great, Gregory of Nazianzus and Gregory of Nyssa we find a few women. They came from diverse backgrounds. Some of them devoted their lives to the service of God, others were lay people. This article seeks to present a part of the bishops’ correspondence and answer questions concerning its female audience. The letters were divided into three groups: 1) consolatory ones; 2) parenetic ones; 3) and the rest of them, that because of their thematic variety were grouped together.